2007
DOI: 10.1111/j.1445-2197.2007.04037.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Functioning Parathyroid Cyst Presenting as a Retrosternal Goitre

Abstract: Parathyroid cysts are rare and even more rarely cause a neck mass resembling a goitre. Such large parathyroid cysts may involve the mediastinum, growing to a sufficient size to produce symptoms related to obstruction, and if functioning, primary hyperparathyroidism. Parathyroid cysts should be considered in the list of differential diagnoses of anterior neck masses to allow for appropriate preoperative investigation to avoid unnecessary confusion at the time of operation. We report a case where a functioning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 20 publications
2
55
0
2
Order By: Relevance
“…Parathyroid cysts are an uncommon entity in the usual clinical setting (1,14,15). The first description of a parathyroid cyst and parathyroid gland in humans was done in 1880 by the Swedish anatomist Ivar Sandström (16)(17)(18), but only in 1905 the first surgical resection was performed by Goris (19) and several years later, Crile in 1953 become the first to diagnose a parathyroid cyst by fine needle aspiration (20).…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroid cysts are an uncommon entity in the usual clinical setting (1,14,15). The first description of a parathyroid cyst and parathyroid gland in humans was done in 1880 by the Swedish anatomist Ivar Sandström (16)(17)(18), but only in 1905 the first surgical resection was performed by Goris (19) and several years later, Crile in 1953 become the first to diagnose a parathyroid cyst by fine needle aspiration (20).…”
Section: Discussionmentioning
confidence: 99%
“…Giant PCs that extend between the lower neck and superior mediastinum are even rarer. McKay et al (11) reported that in all of the PubMed studies that were published since 1925, only 107 giant non-functioning PCs had been reported. The study regarding large parathyroid cystic lesions that was conducted by Rossi et al (12) reported a 0.09% incidence over the last 15 years.…”
Section: Case Reportmentioning
confidence: 99%
“…PCs may be functioning or non-functioning. Nonfunctioning cysts encompass 90 % of cases and occur more commonly in females [13,14]. Functioning cysts usually affect males and are associated with primary HPT [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although most PCs are orthotopic, ectopic localization is possible in the cervical region, including both the thyroid and thymus [15][16][17][18]. Mediastinal PCs are usually large (C4 cm), causing compressive symptoms such as dysphagia and dyspnea [13,19,20], at times mimicking retrosternal goitre [14]. Vocal cord paralysis due to compression on the recurrent laryngeal nerve [21][22][23], respiratory failure and jugular or innominate vein thrombosis have also been reported as complications [24].…”
Section: Introductionmentioning
confidence: 99%